Determinants and Stability of Money Demand in Nigeria - Nwude, E. Chuke; Offor, K. Onochie; Udeh, Sergius N. (International Journal of Economics and Financial Issues, 2018)
This study examines the determinants of broad money demand and its stability in Nigeria over the quarterly period 1991:Q1 to 2014:Q4. With OLS and other statistical methods the results indicate that a long-run relationship exists between the real broad money aggregate and real income, domestic interest rate, inflation rate, exchange rate and foreign interest rate. Real income and exchange rate are directly related to the real broad money balances while domestic interest rate, inflation rate and foreign interest rate are inversely related to the demand for broad money. Keywords: Broad money demand, autoregressive distributed lag, monetary policy, stability, Nigeria. JEL Classifications: C32, E31, E37, F31, O52